Reconfigurable data intensive service for low latency cyber-physical systems and IoT communication - Gupta, Prince; Sharma, Rajeev; Gupta, Sachi (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
The fourth industrial revolution is realized through the many developments in cyber-physical systems (CPS) made possible by the widespread use of the internet of things (IoT). CPS sensor networks must enable mobile and wireless CPSs with their specific flexibility and heterogeneity needs without compromising quality of service (QoS). The research article focuses on reconfigurable data communication hardware for numerous IoT-supporting infrastructures and performance estimation using delay, power, throughput, and packet delivery ratio (PDR) for different IoT node configurations. Tree topology-based network configuration from cloud data to sensor fog organizers, sensor network directors, and IoT-embedded sensors is supported. Functional simulation is performed in iFoGSim, Xilinx ISE, and Modelsim 10.0 with a maximum of 64 variable nodes programmed for data communication and interplay verification with a minimum delay of 9.1 ns, maximum frequency of 319 MHz, power of 7.5 mW, throughput of 0.280, and maximum PDR=1. The simulation is applicable for fog computing and CPS processed from different alters in specific topologies.